Effectiveness of home bleaching treatment after resin infiltrant application - Rocha, Rafael Santos [UNESP]; de Souza, Maurfcio Yugo [UNESP]; Meirelles, Laura Celia Fernandes [UNESP]; Scarense, Carolina Gigli Torres [UNESP]; Diniz, Michele Baffi; Caneppele, Taciana Marco Ferraz [UNESP]; Bresciani, Eduardo [UNESP] (My University, 2020)
Purpose: Resin infiltration may be a barrier for bleaching gels. The aim of this study was to compare dental bleaching effectiveness using low-concentration gels on heavily or mildly stained teeth that were or were not treated with resin infiltration agents. Materials and Methods: Forty bovine enamel surfaces were submitted to demineralisation, after which two staining protocols were performed. Twenty specimens were immersed in a staining broth for 24 h (Lab 1) or 7 days (Lab 2). Ten specimens of each group received resin infiltrant application following the manufacturer's recommendation. All specimens were bleached using 15% carbamide peroxide gel for 14 days (8 h daily). Colour measurement was performed using a reflectance spectrophotometer at three time points: baseline, after staining, and after bleaching. Data (CIEDEOO) were analysed using Student's t-test (p < 0.05). Results: No statistically significant differences were observed in Lab 1 (p = 0.560). For Lab 2, statistically significant differences were detected (p = 0.031). Once bleaching was achieved to some degree (Lab 2), the resin infiltrant may have behaved as a semipermeable barrier to the carbamide peroxide gels. Conclusion: Bleaching treatment was effective on mildly pigmented tooth surfaces. On the other hand, in comparison to the control group, the heavily pigmented surfaces bleached less in the presence of the resin infiltrant, possibly due to the lack of free radicals penetrating into the substrate.
Keywords: Aesthetics; Colour; Dental caries; Dental white spots; Tooth bleaching